Development of Crispy Brownies As A Protein Source Made From Soybean Flour and Red Bean Flour As A Supplementary Food For Pregnant Women - Ramadhani, Fachrunisa; Khoiriyah, Nur; Permatasari, Leya Indah (Urecol Journal. Part C: Health Sciences, 2025)
The prevalence of pregnant women suffering from chronic energy deficiency (CED) in Indonesia remains a public health issue. Pregnant women experiencing CED may face complication related to pregnancy and are at risk of giving birth to low birth weight (LBW) infants. LBW is one of the risk factors for children to experience stunting. The protein needs of pregnant women can be fulfilled by utilizing plant-based food sources. Plant-based food have the potential to be used as additional protein sources. This research aims to develop a crispy brownie product using soybean flour and red bean flour as a source of protein food. The research design used a Complete Randomized Design (CRD) with 4 treatments and 2 replications. The treatments applied were the use of a base material of soybean flour and red bean flour with F1 (90%:10%), F2 (80%:20%), F3 (70%:30%), F4 (60%:40%). The analyses conducted were organoleptic characteristics, chemical analysis, nutrient contribution and production costs. Data analysis used the Kruskal wallis test and the Man-whitney follow up test. The hedonic quality results significantly differ in the color and texture parameters. Meanwhile, the hedonic test significantly differs in the color parameter. F2 is designated as the selected formula. The selected brownies crispy formula contains 4.3% moinsture content; 3,9% ash content; 26.5% protein; 39,3% fat; 30,2% carbohydrates. One serving of brownies crispy contributes 406 kcal of energy. Brownies crispy made from soy flour and selected red bean flour meet the requirements to claim as a source of protein. It is hoped that brownies crispy made from soybean flour and redbean flour can serve as a supplementary food source of protein for pregnant women